Latitudinal distributions of carbonyl sulfide (COS) over mid-high latitude in the Nothern Hemisphere - Yayoi Inomata; Katsuji Matsunaga; Kazuo Osada; Masaharu Watanabe; Yasunobu Iwasaka (National Institute of Polar Research, 2001)
Concentrations of COS in the stratosphere and troposphere were determined from grab samples collected at altitudes ranging from 0.3–12 km during an aircraft flight over mid-high latitude in the Arctic Airborne Measurement Program 1998 (AAMP 98). Concentrations of COS in the troposphere were almost constant within the range of 378-433 pptv. Taking into account the lower abundance of CS2, the photochemical production of COS from CS2 oxidation was less for atmospheric COS north of 53°N. In the stratosphere below 12 km altitude, average concentrations of COS were lower than those in the troposphere. However, concentrations of COS decreased with increasing altitude 1–2 km above the tropopause. It is thought that the phototchemical oxidation of COS in the lowest part of the stratosphere was less during the observation period.